The Nazis - Lace, William W. (San Diego, CA : Lucent Books, 1998)
A history of the Nazi movement in Germany beginning in 1919 with the German Workers' Party and including discussion of Adolf Hitler, anti-Semitism, and World War II.
Includes bibliographical references (p. 99-104) and index.
Keywords: Hitler, Adolf, -- 1889-1945 -- Juvenile literature; Hitler, Adolf, -- 1889-1945.; National socialism -- Juvenile literature; National socialism; Germany -- History -- 1933-1945 -- Juvenile literature; Germany -- History -- 1933-1945.